'Peace throughout the oceans and seas of the world': British maritime strategic thought and world order, 1892–1919. Issue 265 (21st May 2021) - Halewood, Louis
Abstract: Prior to 1914, British strategic thinkers considered the question of how to maintain British world power in the twentieth century. They developed visions of co-operation at sea between not only Britain and the Dominions, but also other states in the international system. During the First World War, these ideas merged with plans for the League of Nations, which British policymakers envisaged as a tool for enforcing peace through the use of sea power. This article explores these ideas, providing a different interpretation of the origins of the League, and the maritime strategic thought of key individuals including Halford Mackinder.